Analysis of energy demand for natural gas sweetening process using a new energy balance technique. (18th June 2018) - Nourmohamadi Taemeh, Alireza; Shariati, Ahmad; Khosravi Nikou, Mohammad Reza
ABSTRACT: Absorption by alkanolamine solvents is widely used for acid gas removal in natural gas sweetening plant. In the present research, one of the Iranian gas treating unit, Ilam Gas Treating Company (IGTC), with 3.27 mole % H2 S and 3.76 mole % CO2 in the inlet feed gas was simulated using HYSYS V8.8. Piperazine activated solution of MDEA (PZ-MDEA) at various process operating conditions was examined to yield energy demand of natural gas sweetening process using a new energy balance technique. In this technique, the total required energy demand was related to three sections: 1. heat of vaporization, 2. sensible heat and 3. heat of the absorption. Energy balance of the absorption and regeneration columns brings a perspective of energy distribution in the sweetening plant. The effects of CO2 and H2 S concentration at inlet feed, PZ mass fraction in activated solution of MDEA and lean amine temperature on energy distribution of the natural gas sweetening process and reboiler duty were investigated. It was finally elucidated that energy demand in the gas sweetening process or duty of reboiler is greatly influenced by heat of vaporization rate. It was also found that the heat of absorption and sensible heat have minor impacts on the energy demand.